Two LRR-Only Proteins Involved in Antibacterial Defense and Prophenoloxidase System of Swimming Crab Portunus trituberculatus - Zhang, Ao; Liu, Yuan; Guo, Na; Li, Shihao; Li, Fuhua (Frontiers in Marine Science, 2022)
The leucine-rich repeat (LRR) motif is evolutionarily conserved in many pattern recognition receptors. Compared to the reported LRR proteins with multiple functional domains, the role of LRR-only proteins merely containing LRR motifs remain largely unexplored. In this study, two LRR-only proteins, PtLRR1 and PtLRR2, were identified from the swimming crab Portunus trituberculatus. Five LRR motifs with a consensus sequence LxxLxxLxLxxNxL were found in their encoded peptides. Both PtLRR1 and PtLRR2 were dominantly expressed in the hepatopancreas and showed a time-dependent response post bacteria and virus stimulation. The recombinant PtLRR1 could bind to various PAMPs, including LPS, PGN, and GLU. PtLRR1 and PtLRR2 displayed different regulatory activities in inducing the expression of inflammation and proPO system-related genes. Knockdown of PtLRR2 led to the decreased expression of the tested cytokines and adapter, while PtLRR1 knockdown enhanced the expression of serine proteases, serine protease homologues, and proPO genes. In addition, knockdown of PtLRR1 or PtLRR2 reduced the clearance activity of Vibrio but upregulated the expression levels of AMPs and key genes of Toll, IMD, and JNK pathways. These results suggest that PtLRR1 and PtLRR2 could act as potential immune receptors and regulate antibacterial immunity in crab.